Development of Drum Brake Pad Material Motorcycle Based Composite Hazelnut Shells, Aluminum and Pineapple Leaf Fibers with Polyurethane Matrix - Isranuri, Ikhwansyah; Adan Silalahi, Jepri; Wirjosentono, Basuki; ., Warman (International Journal of Engineering and Technology, 2019)
This study aims to determine the mechanical properties of composite materials which consist of hazelnut, aluminum and pineapple leaf fibers with polyurethane matrix. Therefore, the properties of flexural strength, hardness, wear rate, heat resistance and microstructure of drum brake pad materials motorcycle should be investigated. The process used for brake pad specimen preparation was casting method, and is compressed by 19 tons. The variation of the material composition divide into 50, 60, 70 and 80 % of filler weight consist of hazelnut shell, aluminum and pineapple leaf fiber with the polyurethane matrix. The size of the hazelnut shell is 100 mesh, aluminum is less than 230 mesh and pineapple leaf fiber around 5 to 10 mm. By the experimental test compared with the microstructure observation, the best composition in consonance with requirement of brake pad composite material is 70 % filler. The composition of 70 % of fillers obtained by density of 1.677 g.cm-3, flexural strength of 11.331 N.mm-2, hardness of 86.8 Rockwell, wear rate of 0.084 mm3.s-1 and heat resistance up to about 260 0C.
Keywords: .